Delivering a lifestyle and weight loss intervention to individuals in real-world mental health settings: lessons and opportunities - Yarborough, Bobbi Jo H (Springer-Verlag, 2011)
Most weight loss interventions for obesity-related risks 11 exclude people with serious mental health conditions. Our goal was to adapt a successful lifestyle/weight loss intervention for this population, deliver it in mental health clinics, and concurrently measure implementation factors. Developmental and implementation-focused formative evaluations guided adaptations and identified barriers/facilitators to successful program deployment. Adaptations included content specific to the population's needs, consciousness-raising among clinicians and patients, additional case management, and greater program flexibility. Barriers included instability in both settings from different sources. Facilitators included familiarity with groups, manual integrity, and appreciation of the program. It was delivered consistently across settings with maximum exposure and fairly good fidelity to the protocol (mean rating = 1.7, 2.0 = complete fidelity). This mixed-method implementation evaluation demonstrated that lifestyle/weight loss interventions in mental health settings are complex, but feasible, and valued by participants. Main program outcomes will be reported at the trial's conclusion.